Ultrasound diagnosis of cervical lymph node metastases in patients with first diagnosed papillary thyroid cancer and in patients previously treated surgically and admitted for radioactive iodine therapy - V. S. Parshin; A. D. Kaprin; S. A. Ivanov; A. A. Veselova; P. I. Garbuzov; V. S. Medvedev (Исследования и практика в медицине)
Purpose of the study. To evaluate the potentialities of ultrasound method in diagnosing cervical lymph node metastasis in patients with first diagnosed papillary thyroid cancer (group 1) and in patients previously treated surgically at different clinics of the Russian Federation and subsequently admitted to the A.F.Tsyb Medical Radiological Research Center — Branch of the National Medical Research Radiological Center to receive radioactive iodine therapy (group 2).Patients and methods. Patients with PTC were divided into two groups. Group 1 included 649 patients with first diagnosed PTC. All the patients underwent thyroidectomy and level VI lymph node neck dissection at the clinic of the A.F.Tsyb Medical Radiological Research Center — Branch of the National Medical Research Radiological Center. Of these patients, 92 patients underwent cervical lymph node dissection including levelsII–III–IV and 9 patients underwent cervical lymph node dissection including level VB. Group 2 consisted of 2875 patients who had previously received surgery at different clinics of the Russian Federation. Subsequently, they were admitted to our institution to receive radioactive iodine therapy. In 291 of these patients, cervical lymph node metastases were found and reoperations were performed: in 89 cases at level VI, in 170 cases at levels II–III–IV and in 32 cases at level VB. The detected metastases were verified histologically.Results. Histology confirmed the presence of nodal metastasis in 57.6% of 649 patients in group 1, and in 10.1% of 241 patients in group 2. In group 1, the incidence of metastatic disease in level VI nodes was 73% and in group 2, it was 30.6%. Metastases in levels II–III–IV were noted in 24.6% of patients in group 1, and in 58.4% of patients in group 2. Level VB metastasis was found in 2.4% of patients in group 1, and in 11% of patients in group 2. Multiple metastases were detected in 75.4% of patients in group 1, and in 20.3% of patients in group 2.Conclusion. Central lymph node metastasis was observed in 73% of patients who were first diagnosed with PTC and treated with thyroidectomy and prophylactic level VI cervical lymph node dissection. In group 2, solitary metastases to lateral lymph nodes occurred more frequently after surgical treatment for PTC, which suggested that the primary treatment was insufficiently radical.